Improved Method of Detection Falsification Results the Digital Image in Conditions of Attacks - Kobozeva A.A.; Grigorenko S.N. (Problems of the Regional Energetics)
The modern level of information technologies development has led to unheard ease embodiments hitherto unauthorized modifications of digital content. At the moment, very important question is the effective expert examination of authenticity of digital images, video, audio, development of the methods for identification and localization of violations of their integrity using these contents for purposes other than entertainment. Present paper deals with the improvement of the detection method of the cloning results in digital images - one of the most frequently used in the software tools falsification realized in all modern graphics editors. The method is intended for clone detection areas and pre-image in terms of additional disturbing influences in the image after the cloning operation for "masking" of the results, which complicates the search process. The improvement is aimed at reducing the number of "false alarms", when the area of the clone / pre-image detected in the original image or the localization of the identified areas do not correspond to the real clone and pre-image. The proposed improvement, based on analysis of different sizes per-pixel image blocks with the least difference from each other, has made it possible efficient functioning of the method, regardless of the specificity of the analyzed digital image.